Pengembangan E-Modul pada Proses Pembelajaran Gardu Induk di Sekolah Menengah Kejuruan - Nomika Febdina; Ali Basrah Pulungan (Jurnal Pendidikan Teknik Elektro, 2021)
This study discusses the development of an E-Module in the subject of the TJTL class XI substation at SMK. E-learning module aims to be used for independent learning. Based on the current conditions hit by the Covid-19 pandemic, schools have stopped face-to-face learning and replaced it with online learning from their homes. So it is important to have a breakthrough in learning, namely learning media that can be accessed online that are used by students so that students can learn independently and understand the subject matter. The purpose of this study is to develop a valid and practical e-module for learning. Based on the research results, the validity of e-module learning from three validators consisting of two expert lecturers and one subject teacher obtained an average achievement level of 87% with the valid category. The practicality test with respondents consisting of one substation subject teacher obtained an achievement level of 93% in the very practical category and respondents consisting of 9 students of class XI TJTL obtained an average achievement level of 88% with the very practical category. From the research data described, it can be concluded that the E-Module learning in the subject of the TJTL class XI substation at SMK is valid and practical.